اصطناع مركبات جديدة للحلقات غير المتجانسة (تيازول، تياديازول، تيازوليدينون، أزوليدينون) مرتبطة مع الفلورين ودراسة الفعالية المضادة للبكتيريا لها - أحمد ثورة; وسوف حسن (Tishreen University Journal -Basic Sciences Series, 2017)
قمنا بتصنيع بعض المركبات الجديدة بدءاً من 2-استيل فلورين وبارا فينيلين دي أمين حيث تم تحضير أساس شيف جديد المركب (1) بدءاً من (2-أستيل الفلورين/ بارا فنيلين دي أمين) عبر تفاعل التكاثف، ثم حضر صباغ آزو ميتين فلوريني المركب (2) ونتج عنه أساس شيف جديد المركب (3) بدءاً من أساس شيف المحضر سابقاً من خلال تفاعل تكاثف بين أساس شيف و5،2- ثنائي هيدروكسي بنز ألدهيد. حضرنا أساس شيف جديد المركب (4) بدءاً من (أساس شيف المحضر سابقاً المركب (1) و5،2- ثنائي هيدروكسي بنز ألدهيد) عبر تفاعل التكاثف. ثم حضرنا مشتقات فلورينية جديدة لحلقة β-اللاكتام المركب (5) ولحلقة التيازوليدينون-4 المركب (6) بدءاً من أساس شيف المحضر سابقاً المركب (4) مع كل من كلورو أستيل كلورايد ومركبتو حمض الخل على الترتيب عبر تفاعلات التحلق. تم تحضير أساس شيف جديد بدءاً من (2-أستيل الفلورين /أمين أولي) عبر تفاعل تكاثف 2-استيل الفلورين مع كل من 5-نترو-2-أمينو تيازول وأدى هذا التفاعل إلى تشكل المركب (7)، كما حضرنا بدءاً من المركب الأخير مع كل من استيل كلورايد والتيويوريا المركبين (8) و(9) على الترتيب بمرود جيد. تم تحضير أساس شيف جديد المركب (10) بدءاً من (2-استيل الفلورين/أمين أولي) عبر تفاعل تكاثف 2-استيل الفلورين مع 5-أمينو-4,3,1– تياديازول-2-تيول. تم تحضير مجموعة من أسس شيف الجديدة بإدخال مستبدلات مختلفة على ذرة الكبريت في الموقع 2 من حلقة التياديازول بدءاً من المركب (10) المحضر سابقاً عبر سلسلة من تفاعلات الاستبدال فحصلنا على المركبات (11,12,13,14)، وأخيراً تم تحضير المركب (15) عبر تفاعل تحلق بدءاً من المركب(14) مع مركبتو حمض الخل. جميع المركبات المحضرة تمت بطريقة التقطير المرتد. جميع المركبات المحضرة لاتنحل بالماء لكنها تنحل بالميتانول والكلوروفوم وثنائي ميتيل سلفوكسيد. تم تحديد بنية المركبات والتعرف عليها باستخدام تحليل أطياف IR و1H-NMR و13C-NMR وLC-MS. Aseries of Schiff base and their derivative (fluorene) have been synthesized primary amines was condensed with 2-acetyl fluorene in DMF (dimethyl formamide) in the presence of conc. HCl acid as catalyst to yield the Schiff base (1). The Schiff base (2,3) and (4) were prepared from the reaction of Schiff base (1) with 2-hydroxy-5-methyl-1,3-benzenedicarboxaldehyde and 2,5-dihydroxy benzaldehyde respectively. and The Schiff’s base (4) was treated with monochloroacetyl choride to give 1- substituted-4(2-fluorenyl)-3-chloro Azolidine-2-on (5). and with α-mercaptoactic acid to gave 3-substituted-2(2-fluorenyl) Tiazolidine-4-on (6). Three series of Schiff Bases and 2,3-disubstituted-1,3-thiazolidin-4-one derivatives. The first series of new Schiff Bases was synthesized by reaction of primary amine (5- nitro,2-amino thiazole) was condensed with aromatic ketone (2-acetyl fluorine) in DMF (dimethyl form amide) in the presence of conc. HCl acid as catalyst to yield the Schiff base (7,8.9). Two series of Schiff Bases and 2,3-disubstituted-1,3-thiazolidin-4-one derivatives were synthesized by reaction of (5- amino-1,3,4-thiadiazole,2-thiole) with (2-acetyl fluorene) in DMF in the presence of conc. HCl acid as catalyst to yield the Schiff base (IV). The Schiff base (10) with α-chloro acetic acid gave compound (11). Esterification of carboxylic moiety of compound (11), using absolute methanol in the presence of conc.H2SO4 yielded a corresponding ester (12), which was condensed with hydrazine hydrate to give acid hydrazide (13). The new Schiff bases (14) were synthesized by reaction of acid hydrizide with terephthalaldehyde in the presence of glacial acetic acid. The thiazolidinone derivatives (15) have been obtained from the azomethines through the addition of α-mercapto actic acid. The structures of synthesized compounds has been established on the basis of their spectral (FT-IR, Mass, 1H, 13C-NMR, elemental analysis) data. The purity of the compounds was confirmed by TLC.